2009
DOI: 10.1002/humu.21038
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2gene variation and its contribution to Parkinson disease

Abstract: Mutation in the LRRK2 gene is a known genetic cause of Parkinson disease (PD). However, due to the high frequency in which the most frequent LRRK2 mutation is present and the large size of LRRK2 gene, a complete sequence-based screening of the entire coding region has only been performed by a few researchers. In addition, normal variability in the LRRK2 gene has only been fully assessed in the North American population. Although a complete examination of the entire gene is required to assess the exact contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
60
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 95 publications
1
60
0
Order By: Relevance
“…Although the variant was initially registered as a nonsynonymous single-nucleotide polymorphism, a subsequent study on the comprehensive sequencing of LRRK2 concluded that this variant should be a mistake in the consensus human genome sequence because it was present in all the cases and controls in their study. 33 The present study further supports the above conclusion that the consensus amino acid at position 50 in LRRK2 protein is histidine instead of arginine. Future studies on the mutational analysis for LRRK2 should take these results into account.…”
Section: Discussionsupporting
confidence: 89%
“…Although the variant was initially registered as a nonsynonymous single-nucleotide polymorphism, a subsequent study on the comprehensive sequencing of LRRK2 concluded that this variant should be a mistake in the consensus human genome sequence because it was present in all the cases and controls in their study. 33 The present study further supports the above conclusion that the consensus amino acid at position 50 in LRRK2 protein is histidine instead of arginine. Future studies on the mutational analysis for LRRK2 should take these results into account.…”
Section: Discussionsupporting
confidence: 89%
“…The K157 amino acid of RAB7L1 lies in the Rab domain (8-176 amino acids) of the protein, which is predicted to be highly conserved among species and is also conserved among other Rab proteins such as RAB1A, RAB3A, RAB7A and RAB8A proteins (data not shown). Molecular links between PD and Rab proteins were already suggested: mutations in the Ras-like GTPase domain of dardarin cause PD 9,18 and elevated expression of RAB1, RAB3A and RAB8A proteins protects against alpha-syninduced dopaminergic neuronal loss in animal models of PD. 19,20 SLC41A1 is a Mg (2+) transporter that may have a role in magnesium homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Taken together, PD is a complex genetic disorder in which the prevalence of some pathogenic mutations may vary widely within ethnicities. 8,9 Genome-wide (GW) SNP genotyping assays have been proven to be a powerful technique to identify genetic risk factors in many complex disorders. 10 Consequently, three large PD-associated genome-wide association studies (GWAS) from two European ancestry and one Asian population have recently identified genetic risks underlying PD, of which SNCA (all three studies) and MAPT (only European ancestry studies) loci showed the strongest evidences of association with PD; [11][12][13] these associations have recently been corroborated by a meta-analysis carried out in European ancestry PD-associated GWAS.…”
Section: Introductionmentioning
confidence: 99%
“…[26]. Furthermore, common polymorphisms within two of these genes (SNCA and LRRK2) are now wellͲassociated to risk factors for common sporadic PD [2,55], which suggests that the contribution of genetics to PD may be more relevant than previously thought.…”
Section: Sporadic and Familial Forms Of Pdmentioning
confidence: 99%